High Market - Schütz, Carl, 1745-1800 (artist):::Creator:::::::::::: (Austria; Vienna; Artaria u. Comp)
Color engraving based on the drawing by Carl Schütz with view of the Hohemarkt (Hoher Markt) in Vienna, including the fountain (Vermählungsbrunnen), with people, horseback riders, carriages, and dogs in the square.